The Arctic Temperature Response to Global and Regional Anthropogenic Sulfate Aerosols - Asutosh, Acharya; Fadnavis, Suvarna; Nuncio, M.; Müller, Rolf; Tripathy, Sarat C. (Frontiers in Environmental Science, 2021)
The mechanisms behind Arctic warming and associated climate changes are difficult to discern. Also, the complex local processes and feedbacks like aerosol-cloud-climate interactions are yet to be quantified. Here, using the Community Earth System Model (CAM5) experiments, with emission enhancement of anthropogenic sulfate (1) five-fold globally, (2) ten-times over Asia, and (3) ten-times over Europe we show that regional emissions of sulfate aerosols alter seasonal warming over the Arctic, i.e., colder summer and warmer winter. European emissions play a dominant role in cooling during the summer season (0.7 K), while Asian emissions dominate the warming during the winter season (maximum ~0.6 K) in the Arctic surface. The cooling/warming is associated with a negative/positive cloud radiative forcing. During the summer season increase in low–mid level clouds, induced by sulfate emissions, favours the solar dimming effect that reduces the downwelling radiation to the surface and thus leads to surface cooling. Warmer winters are associated with enhanced high-level clouds that induce a positive radiative forcing at the top of the atmosphere. This study points to the importance of international strategies being implemented to control sulfate emissions to combat air pollution. Such strategies will also affect the Arctic cooling/warming associated with a cloud radiative forcing caused by sulfate emission change.